Efeito crônico da adição de vibração localizada ao treinamento de força dinâmica máxima - Marcos Daniel Motta Drummond (2017)
The addition of mechanical vibration to strength training may increases maximal strength andmuscle hypertrophy. The objective of the present study was to compare the chronic effect ofdynamic strength training with the addition of local mechanical vibration on maximal strength andhypertrophy of the elbow flexor muscles in individuals recreationally trained. The sample consistedof 20 males, mean age 22.7 ± 5.2 years and mean strength training history of 24.17 ± 11.8 months.After familiarization with the proposed tests and exercises, the subjects were separated into twogroups and submitted to dynamic strength training for 12 weeks. One group performed the strengthtraining program with addition of local vibration (GV), while the other group performed the sametraining program without addition of vibration (GSV). The program consisted of elbow flexionexercises in the orthostatic position and the Scott bench, with 5 sets of 3 to 4 repetition maximum ineach exercise, with a pause of 120 seconds between sets, three times a week. The parameters of thevibration applied during strength training: frequency of 26 Hz and amplitude of 6 mm. Prior to thebeginning of the training period, the volunteers were submitted to one-repetition maximum test(1RM), maximal voluntary isometric contraction (MVIC) and ultrasound to check the thickness ofthe elbow flexor muscles. After the training period, the volunteers were again submitted to strengthtest and ultrasound to determine the chronic effect of strength training to maximal strength andmuscle hypertrophy. The GSV showed significant increases in the means of the 1RM test results inthe exercises of elbow flexion in the orthostatic position (p <0.0001) and the Scott bench (p<0.0001). The GV also showed significant increases in the mean 1RM test results in the exercisesof elbow flexion at the orthostatic position (p <0.0001) and the Scott bench (p <0.0001). Theincreases in maximal dynamic strength presented by the groups were similar in elbow flexion in theorthostatic position (p = 0.250) and in the Scott bench (p = 0.384). The GSV presented a significantincrease in the mean results of the MVIC test after training (p <0.0001), as well as the GV (p<0.0001). The difference between the increases in MVIC presented by the groups was notsignificant (p = 0.212). GSV presented a significant increase in mean muscle thickness aftertraining (p = 0.001), as well as the GV (p = 0.001). No significant difference was found between theincreases in muscle thickness presented by the groups (p = 0.38). Therefore, the results showed thatthe addition of local vibration to the dynamic training of maximal strength did not potentiate thechronic adaptations acquired by recreationally trained men